Gilbertaster caribaea - Mah, Christopher L. (Zenodo, 2020)
Gilbertaster caribaea (Verrill 1899) Figure 12 A–E Observations made during expedition EX1903L2 are the first living observations of this species alive and in several cases, feeding. These individuals were recognized based on the elongate shape of the interradial marginal plates, the dense cover of coarse granules covering the marginal plates as well as the elongate arm shape. The image of the oral surface showed the distinctive series of bivalve pedicellariae present adjacent to the tube foot groove. The collected specimen is largely consistent with the description of the species as outlined in Mah et al . (2010). Gilbertaster (formerly Hippasteria ) caribaea was assigned to Gilbertaster by Mah et al . (2010). Prior to that, Gilbertaster was known only from the Pacific. Video observations detailed herein confirm speculation of Gilbertaster as a corallivore. Color in life for this species is orange. Feeding & Ecological Observations Four observations of Gilbertaster caribaea feeding on primnoid octocorals were made (Figs 12 A–D). Two of these octocorals were identified as Plumarella sp. (12A,B). Feeding behavior for this species is similar to other octocoral predators in that the body is positioned over the octocoral so that its stomach can be directly applied onto the prey. Primnoids appear to show a more frond-like, softer morphology relative to isidid octocorals and appear to be more actively engulfed by the sea stars rather than climbed upon as seen in Circeaster and Evoplosoma . Deep-Sea Amphipod Association Two independent observations of Gilbertaster caribaea have shown 6 to 8 purple amphipods present in association with the tube feet and the oral surface (Fig. 12A,E). The first observation from Richardson Ridge at 797 m, (Fig. 12A) shows Gilbertaster feeding on Plumarella , a primnoid octocoral with its cardiac stomach and tube feet extended onto the prey item. Amphipods were observed in contact with the Plumarella stalk as well as folds of the stomach. It was unclear if they were simply hanging onto the star or the prey item or if they were feeding. A second observation was made on the Central Plateau Scarp at 886 m (Fig. 12E) and showed at least six amphipods irregularly distributed around the oral surface of an individual sitting on its side with its oral surface facing into the water. All of these amphipods were situated either on or adjacent to the tube foot grooves of the animal. The Richardson Ridge observations suggest commensalism or kleptoparasitism by the amphipods on the star as it devours the octocoral tissue. Alternative explanations include predation on the star’s tissue (i.e. stomach and/or tube feet) or even defense by the amphipods against the predator. Glynn (1983) described crustacean “guards” as host symbionts of shallow-water tropical coral, which defend their hosts against attacking sea stars by snapping and pinching. The Central Plateau Scarp observation showed the animal with its oral surface, including tube feet presented upwards into the water. This might represent the animal attempting to divest itself of the amphipods, assuming that present deleterious effects to the star, or are a source of irritation. The numerous pedicellariae on the surface of Gilbertaster might represent a defensive mechanism against these amphipods and/or other small crustaceans. Interestingly, Gale et al . (2013) noted amphipods as part of the stomach contents in Hippasteria phrygiana , another deep-sea hippasterine corallivore. They attributed these amphipods to occasional bottom feeding by H. phrygiana. It is unclear if the amphipods observed on Gilbertaster demonstrate similar behavior to those seen in the gut contents of Hippasteria phrygiana and whether the amphipods presence in the gut might be explained by the behavior observed in the deep-sea species on Gilbertaster . Images Examined On Plumarella Richardson Ridge, Gulf of Mexico, 31.769835, -77.362993, 797 m EX1806_IMG_20180621T193141Z_ROVHD.jpg (amphipods) EX1806_IMG_20180621T193400Z_ROVHD.jpg Also feeding on Plumarella ? Richardson Ridge, Gulf of Mexico, 31.770062, -77.363763, 782 m, EX1806_ IMG_20180621T205519Z_ROVHD.jpg, On octocoral Richardson Ridge, Gulf of Mexico, 31.769577, -77.363013, 781 m EX1806_IMG_20180621T195555Z_ROVHD.jpg Central Plateau Scarp. (with amphipods on oral surface), Off SE coast of United States. 30.923732, 78.087175, 901 m, EX1903L2_IMG_20190629T155659Z_ROVHD.jpg wrapped around coral. Central Plateau Scarp, off SE coast of United States. 30.924116, -78.087582, 886 m, EX1903L2_IMG_20190629T162255Z_ROVHD.jpg. Specimen Examined : USNM 1580844 Richardson’s Jellyfish, 32.0891, -77.6703, 592 m, Coll. A. Weinnig, with ROV Deep Discoverer , aboard NOAA Ship Okeanos Explorer. EX1903L2_IMG_20190701T195409Z_ROVHD. jpg 1 wet spec. R=8.0 r=2.6 : Published as part of Mah, Christopher L., 2020, New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer, pp. 201-260 in Zootaxa 4766 (2) on pages 228-230, DOI: 10.11646/zootaxa.4766.2.1, http://zenodo.org/record/3764018 : {"references": ["Verrill, A. E. (1899) Revision of certain genera and species of starfishes, with descriptions of new forms. Transactions of the Connecticut Academy of Arts and Sciences, 10 (1), 145 - 234. https: // doi. org / 10.5962 / bhl. part. 7031", "Mah, C. L., Nizinski, M. & Lundsten, L. (2010) Phylogenetic Revision of the Hippasterinae (Goniasteridae; Asteroidea): Systematics of Deep Sea Corallivores, including one new genus and three new species. Zoological Journal of the Linnean Society, 160, 266 - 301, 11 figs. https: // doi. org / 10.1111 / j. 1096 - 3642.2010.00638. x", "Glynn, P. W. (1983) Crustacean symbionts and the defense of corals: coevolution on the reef? In: Nitecki, M. H. (Ed.), Coevolution. University of Chicago Press, Chicago, Illinois, pp. 111 - 178.", "Gale, K. S. P., Hamel, J. - F. & Mercier, A. (2013) Trophic ecology of deep-sea Asteroidea (Echinodermata) from eastern Canada. Deep-Sea Research I, 80, 25 - 36. https: // doi. org / 10.1016 / j. dsr. 2013.05.016"]}